Electrodeposition of high hardness and high corrosion resistance Cr-C coating using trivalent chromium bath - Tey, Eydar; Zainal, Zulkarnain; Lim, Kean Pah; Ismail, Ismayadi (Springer, 2025)
This study presents a novel approach to optimizing Cr-C coatings to achieve enhanced microhardness and corrosion resistance, focusing on the interplay between deposition parameters and coating microstructure. Unlike prior studies that often emphasize limited parameter variations, this research provides a comprehensive analysis of the effects of current density, pH, bath temperature, and deposition time on the microstructure and properties of Cr-C coatings. Advanced characterization techniques, including X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), energy-dispersive X-ray spectroscopy (EDX), Vickers microhardness testing, and potentiodynamic polarization scans, were employed to investigate the crystalline structure, surface morphology, composition, mechanical hardness, and corrosion behavior. The key innovation lies in correlating these parameters to achieve coatings with compact grain growth and uniform morphology, resulting in exceptional performance. The study identifies optimal deposition conditions at a current density of 20 A/dm2, pH 1.5, bath temperature of 35 °C, and deposition time of 60 minutes, which yielded the highest hardness and superior corrosion resistance. These findings significantly advance the understanding of Cr-C coating processes and their potential applications in industries demanding high durability and corrosion resistance.